Tingkat Pengetahuan Orang Tua Terhadap Pemakaian Antibiotik pada Anak di Apotek Asia Farma Kabupaten Karanganyar - Ayu Rahmawati Setyo; Sri Saptuti Wahyuningsih; Susi Endrawati (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2023)
In general, antibiotics can be interpreted as chemical substances produced from fungi and bacteria. The incidence of resistance in a person can be triggered by the high enough use of drugs containing antibiotics with improper usage rules. The attitude of a person in this case parents in the use or use of antibiotic drugs, can be reflected in the level of knowledge he has. Efforts to find out the level of knowledge from parents about the use of antibiotics in children at Apotek Asia Farma, became the purpose of this study. This type of research is quantitative descriptive research, by applying cross-sectional research design in determining the sample. Data were collected and analyzed using Microsoft Excel and Statistical analysis with SPSS version 25.0. The instrument as a measuring instrument in this study used a closed questionnaire. All parents of patients or pharmacy visitors were in the population in this study. The number of samples obtained is 85 respondents. The data obtained shows that the most respondents are mothers with a total of 65 people (76.47%), the most age is 26-35 years, which is 34 people (40%), the most recent education is SMA/MA/SMK graduates, as many as 33 people (38.8%), the highest family income is moderate income with a total of 60 people (70.6%). Based on the experience of giving antibiotics the most giving antibiotics to children as many as 76 people (89.4). Respondents with good knowledge were 52 people (61.2%). Respondents with sufficient knowledge were 32 people (37.6%). Respondents with less knowledge were 1 person (1.2%).